UK policy on social networking sites and online health: from informed patient to informed consumer? - Hunt, Daniel; Koteyko, Nelya; Gunter, Barrie (Sage, 2015)
Background: Social networking sites offer new opportunities for communication between and amongst health care professionals, patients and members of the public. In doing so, they have the potential to facilitate public access to health care information, peer-support networks, health policy fora and online consultations. Government policies and guidance from professional organisations have begun to address the potential of these technologies in the domain of health care and the responsibilities they entail for their users.